THE INFLUENCE OF PRODUCT QUALITY, PRICE, AND LAYOUT ON CONSUMER PURCHASE DECISIONS AT THE SHADE OF THE EQUATOR STORE IN JEMBER REGENCY - Sofiatul Hasanah; Izzuddin, Ahmad; Winahyu, Pawestri (Universitas Muhammadiyah Bengkulu, 2025)
Retail business development shows strong potential in the current era. The retail industry delivers products and services while adding value to fulfill the needs of individuals, families, groups, or end users. Most products sold in retail cater to household requirements. The growing retail industry has made a substantial contribution to the Gross Domestic Product (GDP). This study aims to examine and analyze the impact of product quality, price, and layout on consumer purchasing decisions at the Rindang Khatulistiwa store in Jember. This research employs a quantitative approach with a sample size of 100 respondents, using the Non-Probability Sampling Technique combined with purposive sampling and questionnaires as the primary data collection tool. The data analysis process includes instrument validation, classical assumption testing, multiple linear regression, hypothesis testing, and calculation of determination coefficients. The analysis indicates that product quality, price, and layout each exert a positive and significant partial effect on consumer purchasing decisions at the Rindang Khatulistiwa store in Jember, contributing 85%.